Analysis of CRSsNP Proteome Using a Highly Multiplexed Approach in Nasal Mucus. Issue 3 (May 2023) - Pesold, Vanessa-Vivien; Wendler, Olaf; Morgenthaler, Lisa; Gröhn, Franziska; Mueller, Sarina K.
Background: Chronic rhinosinusitis without nasal polyps (CRSsNP) represents a phenotype of CRS, whose immunological mechanisms are still unclear. So far there are neither suitable biomarkers to determine the course of the disease nor an individual therapy. Objective: The purpose of this study was to characterize the CRSsNP endotype by identifying and validating non-invasive proteomic biomarkers. Methods: A highly-multiplexed proteomic array consisting of antibodies against 2000 proteins was used to identify proteins that are differentially expressed in the nasal mucus of the CRSsNP and control groups (n = 7 per group). The proteins identified to be most differentially expressed were validated in matched nasal mucus samples using western blots and enzyme-linked immunosorbent assay (ELISA). Validation was also done in a second cohort using western blots (CRSsNP n = 25, control n = 23) and ELISA (n = 30 per group). Additionally, immunohistochemistry in CRSsNP and control tissue samples was performed to characterize the selected proteins further. Results: Out of the 2000 proteins examined, 7 from the most differentially expressed proteins were chosen to be validated. The validation results showed that 4 proteins were significantly upregulated in CRSsNP mucus, including macrophage inflammatory protein-1beta (MIP-1β), resistin, high mobility group box 1 (HMGB1), and forkhead box protein 3 (FOXP3). Cartilage acidic protein 1 (CRTAC1) was not significantly upregulated. Two proteins were significantly downregulated including scavenger receptor class F member 2 (SCARF2) and P-selectin. All proteins selected are mainly associated with inflammation, cell proliferation/differentiation, apoptosis and cell–cell or cell–matrix interaction. Conclusion: Proteomic analysis of CRSsNP and control mucus has confirmed known and revealed novel disease-associated proteins that could potentially serve as a new biosignature for CRSsNP. Analysis of the associated pathways will specify endotypes of CRSsNP and will lead to an improved understanding of the pathophysiology of CRSsNP. Furthermore, our data contribute to the development of a reproducible, non-invasive, and quantitative "liquid biopsy" for rhinosinusitis.